Marked state graph of machine production system with a stock of crop production units (Science journal «Technical service of agriculture, forestry and transport systems», 2026)
The author proposed analytical approaches to the description of the models of the marked graph of the operation states of the machine production system with a stock of plant production units. The obtained dependencies of the system states make it possible to establish, given the given characteristics of the investigated machines and equipment for the production of crop production, rational modes of providing resources for processing and repairing the equipment in case of technical failures.
Keywords: graph; condition; system; crop production; combine